Wave‐LORAKS: combining wave encoding with structured low‐rank matrix modeling for more highly accelerated 3D imaging - Kim, Tae Hyung; Polak, Daniel (Magnetic resonance in medicine, 2018)
Wave‐CAIPI is a novel acquisition approach that enables highly accelerated 3D imaging. This paper investigates the combination of Wave‐CAIPI with LORAKS‐based reconstruction (Wave‐LORAKS) to enable even further acceleration.